Agent-based approaches in economic and social complex systems VII : Post-Proceedings of The AESCS International Workshop 2012 - Terano, Takao; Takahashi, Shingo; Murata, Tadahiko (Agent-Based Social Systems, 2013)
Agent-based modeling/simulation is an emergent approach to the analysis of social and economic systems. It provides a bottom-up experimental method to be applied to social sciences such as economics, management, sociology, and politics as well as some engineering fields dealing with social activities. This book includes selected papers presented at the Seventh International Workshop on Agent-Based Approaches in Economic and Social Complex Systems held in Osaka, Japan, in 2012. At the workshop, 24 reviewed full papers were presented, and of those, 17 were selected to be included in this volume. The papers are divided into two groups as "Fundamentals of Agent-Based Modeling" and "Applications of Agent-Based Modeling".